Vaccinia virus serpins B13R and B22R do not inhibit antigen presentation to class I-restricted cytotoxic T lymphocytes. - Blake, N; Kettle, S; Law, K; Gould, K; Bastin, J; Townsend, A; Smith, G (1995)
Vaccinia virus (VV) inhibits the presentation of certain epitopes from influenza virus nucleoprotein (NP), haemagglutinin (HA) and non-structural 1 (NS1) proteins to CD8+ cytotoxic T lymphocytes (CTL) by an unknown mechanism. We have investigated whether VV genes B13R and B22R, which encode proteins with amino acid similarity to serine protease inhibitors (serpins), are involved in this process. Recombinant VVs were constructed which express influenza virus proteins HA, NP or NS1 and which lack serpin gene B13R or both B13R and B22R. The lysis of cells infected with these viruses by influenza virus-specific CD8+ CTL was compared to the lysis of cells infected with viruses expressing both the influenza proteins and the serpin genes. Cytotoxicity assays showed that deletion of the VV serpin genes B13R and B22R and other genes between B13R and B24R did not increase the level of lysis, indicating that these genes are not involved in inhibition of antigen presentation of the epitopes tested.